Evaluation of Availability and Implementation of the Compulsory Pharmacy Medicines List: A Case Study at X Pharmacy - Muchromin Muchromin; Ayu Nissa Ainni (Jurnal EduHealth, 2026)
Compulsory Pharmacy Medicines (OWA) represent a crucial policy to ensure public access to certain hard drugs within the framework of safe self-medication, yet its implementation at the pharmacy level often faces various challenges. This study aims to evaluate the availability of OWA and analyze the factors influencing its implementation at X Pharmacy. The research employed an evaluative descriptive design with a cross-sectional approach, using direct observation checklists to assess the physical availability of 58 drug items on the OWA list and structured questionnaires to measure pharmaceutical personnel knowledge, with data analyzed using descriptive quantitative methods. The findings indicate that only 38 drugs (65.52%) were available out of the total 58 OWA items, while 20 drugs (34.48%) were unavailable, with the highest distribution in Group 1 (10 unavailable items), suggesting a significant gap between regulation and implementation at the pharmacy level. The availability of OWA at X Pharmacy does not meet regulatory standards, and the unavailability of drugs, particularly in Group 1, potentially diminishes the pharmacy's role in supporting safe self-medication. These findings highlight the urgent need for systematic efforts in inventory management, capacity building for personnel, and strengthening of monitoring systems to enhance compliance with OWA regulations and improve pharmaceutical service quality in community pharmacies.